Veillonella parvula outer membrane vesicles increase ICAM-1+ neutrophils exhibiting elevated NET formation via ROS–PAD4 signaling - Xu, Lina; Jiang, Yiting; Zhao, Xuri; Zhuang, Jiabao; Chen, Huiwen; Li, Teng; He, Zhiyan; Zhou, Wei; Song, Zhongchen (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundVeillonella parvula (V. parvula), as an anaerobic Gram-negative coccus, produces outer membrane vesicles (OMVs) to promote bacterial colonization and periodontitis progress. Neutrophils are the first immune cells during bacterial stimulation, while neutrophil extracellular traps (NETs) are the early triggers in the progress of periodontitis. However, the interactions between neutrophils and V. parvula are still unknown. Therefore, this study investigated the effects and underlying mechanisms of V. parvula OMVs on neutrophils.MethodsNeutrophil migration, apoptosis, and phagocytosis and reactive oxygen species (ROS) production were assessed following stimulation with V. parvula OMVs. The differential gene expression in neutrophils was characterized using RNA sequencing. The correlation between intercellular adhesion molecule 1 (ICAM-1) expression and NET formation was verified through flow cytometry and immunofluorescence. The NET formation-associated components, including cell-free DNA, neutrophil elastase, myeloperoxidase, and the PAD4 expression were analyzed. The frequencies of the ICAM-1+ neutrophils and NET formation were evaluated in neutrophils pretreated with CYBB or PAD4 inhibitors.ResultsNeutrophils exhibited robust migration, increased apoptosis, and ROS production following exposure to V. parvula OMVs. No significant differences were observed in neutrophil phagocytosis. RNA sequencing analysis revealed a significant increase in the expression of Icam-1 mRNA. And higher ICAM-1+ neutrophils in the V. parvula OMVs group enhanced the levels of NET formation via activation of ROS-PAD4 signaling pathway.ConclusionsV. parvula OMVs were initially found to increase the population of ICAM-1+ neutrophils, which subsequently exhibited elevated NET formation via the ROS–PAD4 signaling pathway. This study elucidates a novel pathogenic mechanism of V. parvula OMVs and highlights the potential of targeting ICAM-1+ neutrophils as a therapeutic approach for chronic periodontitis.